A method to transfer speckle patterns for digital image correlation. (21st July 2015) - Chen, Zhenning; Quan, Chenggen; Zhu, Feipeng; He, Xiaoyuan
Abstract: A simple and repeatable speckle creation method based on water transfer printing (WTP) is proposed to reduce artificial measurement error for digital image correlation (DIC). This technique requires water, brush, and a piece of transfer paper that is made of prefabricated decal paper, a protected sheet, and printed speckle patterns. The speckle patterns are generated and optimized via computer simulations, and then printed on the decal paper. During the experiments, operators can moisten the basement with water and the brush, so that digital patterns can be simply transferred to the carriers' surfaces. Tensile experiments with an extended three-dimensional (3D) DIC system are performed to test and verify the validity of WTP patterns. It is shown that by comparing with a strain gage, the strain error is less than 50 με in a uniform tensile test. From five carbon steel tensile experiments, Lüders bands in both WTP patterns and spray paint patterns are demonstrated to propagate symmetrically. In the necking part where the strain is up to 66%, WTP patterns are proved to adhere to the specimens well. Hence, WTP patterns are capable of maintaining coherence and adherence to the specimen surface. The transfer paper, working as the role of strain gage in the electrometric method, will contribute to speckle creation.